2010
DOI: 10.1080/1360080x.2011.536976
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of perceptions of gender and leadership in Australian and Turkish universities

Abstract: This paper analyses differences in perceptions of gender and leadership though qualitative interviews with 45 senior managers in Australia and Turkey. The literature suggests that masculine models of leadership are changing with both women and many men preferring transformational leadership styles. The research found that there were different perceptions about gender and leadership in Australian and Turkish universities, reflecting different economic and social contexts. Turkish respondents mostly did not enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 24 publications
1
20
1
4
Order By: Relevance
“…This invisibility of gender is part of the assumption of the masculine vision of the world that is predominant in organisational analysis (Bensimon 1993;Coronel Llamas, Moreno, and Padilla 2002), and also of the predominance of theories about leadership that has to do with heroic masculinity. Implicit in such a vision is the claim to protect women while men's positional power is preserved (Kerfoot and Whitehead 1998, 451;White and Özkanlib 2011). For Blackmore and Sachs (2007, 77), while control and power in management, a traditionally masculine field, assume a positive symbolic capital, femininity assumes a negative one.…”
Section: Theoretical Framework: Gender and Leadership In Organisationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This invisibility of gender is part of the assumption of the masculine vision of the world that is predominant in organisational analysis (Bensimon 1993;Coronel Llamas, Moreno, and Padilla 2002), and also of the predominance of theories about leadership that has to do with heroic masculinity. Implicit in such a vision is the claim to protect women while men's positional power is preserved (Kerfoot and Whitehead 1998, 451;White and Özkanlib 2011). For Blackmore and Sachs (2007, 77), while control and power in management, a traditionally masculine field, assume a positive symbolic capital, femininity assumes a negative one.…”
Section: Theoretical Framework: Gender and Leadership In Organisationsmentioning
confidence: 99%
“…Other authors consider that leadership abilities have more to do with situational and contextual variables than with those linked to gender (Ball 2007;Bolden, Petrov, and Gosling 2009;Frenkel and Stretchman 2006;White and Özkanlib 2011). Sensitivity to context, according to Mills (2002, 300), means that 'to understand the gendered subjectivities of the actors involved we need to understand the discourses in which they were located and the relationships in which they were involved'.…”
Section: Theoretical Framework: Gender and Leadership In Organisationsmentioning
confidence: 99%
“…Women university managers also suffer a dearth of development opportunities (Wallace & Marchant, 2009) and a discourse of efficiency and economics has replaced that of equity (Wagner, 2008). This paper focuses on female administrative managers in contrast to academic managers who have been well documented in Australia at senior levels (Blackmore & Sachs 2001;Chesterman, Ross-Smith, & Peters, 2003;Özkanli & White, 2009a;2009b;White & Özkanli, 2011) and in middle management (Wallace & Marchant, 2009), with similar coverage overseas (Doherty & Manfredi, 2006;Ebner, 2007;Gopinathan, 2007;Krefting, 2003;Niven, 2007;Van den Brink, Brouns, & Waslander, 2006). Administrative managers deserve to be studied in their own right due to their pivotal role in teaming with academic staff to provide improved student outcomes in today's regulated and measured, managerialistic environment (Szekeres, 2006).…”
Section: Gender In Higher Educationmentioning
confidence: 99%
“…The late 1990s witnessed the first school leadership studies in Spain to introduce the gender perspective, an approach that attracted increasing research interest in subsequent years (Coronel Llamas, Carrasco Macías, & Moreno Sánchez, 2012; Gómez Delgado & Moreno Sánchez, 2011;Moncayo Orjuela & Pinzón López, 2013;Moncayo Orjuela & Villalba Gómez, 2014;Tomás Folch & Guillamón Ramos, 2009;Wallace & Marchant, 2009;White & Özkanli, 2010;etc.). All these studies have reported a very low percentage of female representation in school leadership positions at all educational levels.…”
mentioning
confidence: 99%
“…Since the 1980s, various studies have employed the term glass ceiling to describe this phenomenon (Coronel Llamas et al, 2012;Eliseo Valle, 2012;Gómez Delgado & Moreno Sánchez, 2011;Tomás Folch & Guillamón Ramos, 2009;White & Özkanli, 2010), using the metaphor of an invisible glass barrier to refer to all those intangible obstacles that block the progress of many women in the labour market and give rise to the vertical discrimination evidenced by the decreasing proportion of women the further up one moves in any organisational pyramid. Other authors have referred to this phenomenon as the sticky floor, since it seems that the floor at the bottom of the pyramid glues women so firmly into place that they are unable to break free and enter higher level positions.…”
mentioning
confidence: 99%